Brave Margaret : an Irish adventure - San Souci, Robert D.; Comport, Sally Wern (New York : Aladdin Paperbacks, 2002)
Presents a retelling of an Irish folktale, wherein a brave young woman battles a sea serpent and rescues her true love from a giant.
Wilson's Children
School Library Journal
Book Links (A.L.A.)
4.6
K-3
Keywords: Fairy tales; Folklore -- Ireland; Fairy tales; Folklore -- Ireland